Hysteroscopic treatment of cervical pregnancy: case report - Valdez, Aarón Jiménez; Flores, Sara Elia Hernadez; Vilchis, Jorge Arturo Barbabosa; Calderon, Claudia Meixueiro (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Of ectopic pregnancies, cervical implantation pregnancy is an exceptional entity, corresponding to less than 1% of ectopic pregnancies. With an incidence calculated at 1: 2500 to 1: 12,000 pregnancies. The risk factors for cervical pregnancy are the same as for other ectopic pregnancies. This entity, a difference from tubaric pregnancy where bleeding is within the peritoneal cavity, the main risk is incoercible vaginal bleeding, which usually ends in a hysterectomy, which limits the reproductive future of patients. There are currently no established criteria for candidates for medical versus surgical treatment. This case reports a case of cervical ectopic pregnancy, treated with Methotrexate, and culminating with hysteroscopy resection.